Prospective study of left ventricular function after radiofrequency ablation of atrioventricular junction in patients with atrial fibrillation. Issue 3 (September 1995) - Edner, M.; Caidahl, K.; Bergfeldt, L.; Darpö, B.; Edvardsson, N.; Rosenqvist, M.
Abstract : BACKGROUND--In patients with drug resistant incessant supraventricular tachycardia, radiofrequency induced ablation of the atrioventricular junction and pacemaker implantation have hitherto been considered a treatment of last resort. OBJECTIVE--To assess the short and long term effects of ablation of the atrioventricular junction on systolic and diastolic left ventricular function in patients with atrial fibrillation with and without impaired left ventricular function. PATIENTS--29 patients (19 men; mean age 65 (SD 7) years (range 50-76)) undergoing ablation of the atrioventricular junction for drug refractory atrial fibrillation were examined a mean of 2, 65, and 216 days after ablation of the bundle of His. MAIN OUTCOME MEASURES--Left ventricular ejection fraction and early filling deceleration times (Edec) were assessed by Doppler echocardiography after 1 to 2 hours of ventricular pacing at a rate of 80 beats/minute. RESULTS--In 14 patients with a left ventricular ejection fraction < 50% left ventricular ejection fraction increased significantly from 32% (11%) to 39% (11%) (65 days) and 45% (11%) (216 days) (P < 0.001); Edec increased from 142 (46) ms to 169 (57) ms (65 days) and 167 (56) ms (216 days) (P < 0.05). In 15 patients with an ejection fraction > or = 50% at the initial examination no significant change in systolic function was observed. CONCLUSIONS--In patients with left ventricular dysfunction long term improvement of systolic and diastolic left ventricular function was seen after ablation of the atrioventricular junction for rate control of atrial fibrillation. This procedure had no adverse effects on normal left ventricular function.